Professional Task-Based Curriculum Development for Distance Education Practitioners at Master’s Level: A Design-Based Research - Feng, Xiaoying; Lu, Guangxin; Yao, Zhihong (International Review of Research in Open and Distributed Learning, 2015)
Curriculum development for distance education (DE) practitioners is more and more focusing on practical requirements and competence development. Delphi and DACUM methods have been used at some universities. However, in the competency-based development area, these methods have been taken over by professional-task-based development in the last decade, which has not been applied in the open and distance education area so far. Is the professional-task-based curriculum development approach suitable for open and distance education? This study aims to develop a Master Degree curriculum for DE practitioners in China based on professional tasks. Design-based research (DBR) was used and two cycles of DBR were conducted. Interviews and observations were used to collect data. In the first round of DBR, the authors find that professional-task-based development is feasible and could direct more closely to practical requirements of competencies, and that meanwhile, this approach has some disadvantages and limitations. In the second round of DBR, the approach was revised and results showed that the revised approach was much more suitable and reasonable for DE practitioners. Results of this study include: 1) professional-task based curricula for DE practitioners in China; 2) a curriculum development approach for open and distance education revised from professional-task-based development.